Safety and efficacy of artesunate-amodiaquine combined with either methylene blue or primaquine in children with falciparum malaria in Burkina Faso: a randomized controlled trial - Müller, Margarida Melo Mendes Jorge; Ouermi, Lucienne; Meissner, Peter; Compaoré, Guillaume; Coulibaly, Boubacar; Nebie, Eric; Krisam, Johannes; Klose, Christina; Kieser, Meinhard; Jahn, Albrecht; Lu, Guangyu; D'Alessandro, Umberto; et al. (PLOS ONE, 2019)
Artemisinin resistance is threatening global efforts for malaria control and elimination. Primaquine (PQ) and methylene blue (MB) are gametocytocidal drugs that can be combined with artemisinin-based combination therapy (ACT) to reduce malaria transmission, including resistant strains. Children (6-59 months) with uncomplicated falciparum malaria in Burkina Faso were treated with artesunate-amodiaquine (AS-AQ) and randomized to MB (15 mg/kg/day for 3 days) or PQ (0.25 mg/kg at day 2) with the aim to show non-inferiority of the MB regimen with regard to haematological recovery at day 7 (primary endpoint). MB-AS-AQ could not be shown to be non-inferior to PQ-AS-AQ (mean Hb difference between treatment groups on day 7 was -0.352, 95% CI -0.832-0.128, p = 0.0767), however, haemoglobin recovery following treatment was alike in the two study arms (day 7: mean 0.2±1.4 g/dl vs. 0.5±0.9 g/dl, p = 0.446). Occurrence of adverse events was similar in both groups, except for vomiting, which was more frequent in the MB than in the PQ arm (20/50 vs 7/50, p = 0.003). Adequate clinical and parasitological response was above 95% in both groups, but significantly more asexual parasites were cleared in the MB arm compared to the PQ arm already on day 1 (48/50, 96%, vs 40/50, 80%, p = 0.014). Moreover, P. falciparum gametocyte prevalence and density were lower in the MB arm than in the PQ arm, which reached statistical significance on day 2 (prevalence: 2/50, 4%, vs 15/49, 31%, p<0.001; density: 9.6 vs 41.1/μl, p = 0.024). However, it should be considered that PQ was given only on day 2. MB-ACT appears to be an interesting alternative to PQ-ACT for the treatment of falciparum malaria. While there is a need to further improve MB formulations, MB-ACT may already be considered useful to reduce falciparum malaria transmission intensity, to increase treatment efficacy, and to reduce the risk for resistance development and spread. Trial registration: ClinicalTrials.gov NCT02851108.